Crossing Central Europe Continuities and Transformations, 1900 and 2000 - Mitterbauer, Helga (German and European Studies, 2017)
This volume studies elements of Austro-Hungarian or Central European culture that were common across linguistic, national, and ethnic communities, and shows how some of these commonalities survived or were transformed by the turmoil of the 20th century: two world wars, a major depression between the wars, Stalinism and the Iron Curtain.